2005
DOI: 10.1007/s00109-005-0703-z
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression studies in prostate cancer tissue: which reference gene should be selected for normalization?

Abstract: Using quantitative reverse transcription-polymerase chain reaction (RT-PCR), reference genes are utilized as endogenous controls for relative quantification of target genes in gene profiling studies. The suitability of housekeeping genes for that purpose in prostate cancer tissue has not been sufficiently investigated so far. The objective of this study was to select from a panel of 16 potential candidate reference genes the most stable genes for gene normalization. Expression of mRNA encoding ACTB, ALAS1, ALB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
185
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(198 citation statements)
references
References 35 publications
10
185
2
1
Order By: Relevance
“…For cDNA synthesis, 1 Ag RNA was reverse transcribed using Expand Reverse transcriptase (Roche), according to the manufacturer's protocol. Samples (5 AL of cDNA in a 50 AL final volume) were used to quantify levels of fer transcripts by real-time PCR relative to levels of succinate dehydrogenase (SDHA) used as a reference housekeeping gene (53). PCRs were carried out using validated primers for Fer (QT00029043) and SDHA (QT00059486) with the QuantiTect SYBR Green PCR Master Mix, according to the manufacturer's instructions (Qiagen), in a MyiQ Single-Color Real-Time PCR Detection System (Bio-Rad).…”
Section: Real-time Pcrmentioning
confidence: 99%
“…For cDNA synthesis, 1 Ag RNA was reverse transcribed using Expand Reverse transcriptase (Roche), according to the manufacturer's protocol. Samples (5 AL of cDNA in a 50 AL final volume) were used to quantify levels of fer transcripts by real-time PCR relative to levels of succinate dehydrogenase (SDHA) used as a reference housekeeping gene (53). PCRs were carried out using validated primers for Fer (QT00029043) and SDHA (QT00059486) with the QuantiTect SYBR Green PCR Master Mix, according to the manufacturer's instructions (Qiagen), in a MyiQ Single-Color Real-Time PCR Detection System (Bio-Rad).…”
Section: Real-time Pcrmentioning
confidence: 99%
“…grade and stage of tumors, and as previous studies indicate, the expression of a reference gene is not directly associated with the grade and stage of malignant tumors (21); the selected samples were all characterized as malignant tissue samples by the pathology department of the China-Japan Union Hospital of Jilin University, and the pathology observed in the samples indicated the most common pathological type of CCA, adenocarcinoma; the QBC939 cell line was also used as it is a commonly used human CCA cell line; the stability evaluation on reference genes for the selected histological samples and cell lines of human CCA was implemented to make the experimental results more comprehensive, compared with previous studies (9,10,21,22) where the stability evaluation on reference genes was restricted on ceratin tissues or cell lines; and the stability of 12 common reference genes was compared.…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, during the detection of target gene expression, a gene with a stable expression is required as a reference. Recent studies have revealed defects in all commonly used reference genes, which often vary greatly in expression quantity in various types of cells and tissues, stages of cell amplification and organ development and in vitro culture and experimental conditions (9,10,(20)(21)(22). To the best of our knowledge, there have been no systematic comparisons performed concerning the stability of commonly-used reference genes in CCA tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reliable reference gene for the transcriptional study in cross-subfamily cloned embryo is necessary for comparative analysis. Previous studies had provided solid evidence that the expression levels of some housekeeping genes varied considerably in diVerent developmental stages and under diVerent experimental conditions [3][4][5]. In the present study, we analyzed GAPDH (glyceraldehyde-3-phosphate dehydrogenase) expression levels both in zebraWsh embryos and in cross-subfamily cloned embryos to determine whether GAPDH could be used as a suitable reference for nuclear reprogramming.…”
mentioning
confidence: 95%